Using Picture Series to Improve the Students’ Ability in Speaking Narrative Text - Deena Dwi Aprilia; Sri Andreani (English Learning Innovation (englie), 2020)
The research aimed at the use of picture series to improve the students’ speaking ability of tenth graders in narrative text. In accordance with the findings of preliminary study which showed that the students’ speaking performance was low, the researcher chose speaking as the focus skill to be improved. The skill was chosen because the students faced many difficulties to perform this skill, such as the lack of vocabulary, the coherence in speaking, and the difficulty to express the ideas. The study applied a classroom action research that was conducted in two cycles consisting of five meetings. The subject of this research was 34 tenth grade students of SMAN 4 Malang. The findings of the research revealed that using picture series improved the students’ speaking score in some aspects of speaking skills, comprising fluency, pronunciation, content, and coherence. Besides, it could make the student eager to be involved in the teaching and learning process.